Analysis of Teachers' Pedagogical Skills in Improving the Quality of Learning in Elementary Schools - Neni Malia; Siti Mayang Sari; Zahraini Zahraini (Dinasti Publisher, 2025)
This study aims to review the implementation of improving teacher pedagogical competence at SD Negeri 2 Seunagan, Nagan Raya Regency. Pedagogical competence is an important ability that must be possessed by every teacher in designing, implementing, and evaluating learning. Based on the results of observations there are teachers who teach using conventional methods. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research informants consisted of five subject teachers. The results of the study indicate that training and support from the principal have a positive impact on improving teacher pedagogical competence, which includes student understanding, curriculum development, designing and implementing educational learning, and evaluating learning outcomes. This finding confirms that the role of teachers provides direct changes to thinking patterns and improving student learning outcomes. Strategic techniques are needed to improve the quality of the learning process in schools through training activities for teachers according to curriculum needs. This study is expected to be a reference for teachers to continue to improve their pedagogical quality through training, active cooperation in schools and character in developing themselves with the quality of learning as professional teachers.